Technology-Based Interactive Learning Media Training for Lecturers - Respati, Dwi Kismayanti; Mardi; Handarini, Dwi; Sumiati, Ati; Susanti, Santi; Zulaihati, Sri; Fauzi, Achmad (Jurnal Pemberdayaan Masyarakat Madani (JPMM), 2023)
The progress of ICT is closely related to teaching and learning activities in an educational institution. Coupled with the distance learning situation, the learning process must be interactive and attract students' interest in learning. To improve the quality of learning, lecturers need to present an innovative and interesting learning media. This community service activity is held to develop the ability of lecturers in teaching through Prezi and Canva media training. The activity was held by virtual zoom and was attended by 48 lecturers from Musi Rawas University, Malikussaleh University and STIEBI Prana Putra. This study uses qualitative methods to observe the object naturally. Participants' performance will be evaluated by pre- and post-tests. The post-test results show an increase in lecturers' skills in mastering Prezi and Canva media. The results of the satisfaction survey also showed that all participants were satisfied with this activity and expected similar activities to be held regularly.